Using of pumpkin and carrot powder in production of meat cutlets: effect on chemical and sensory properties - Kassymov, Samat (International Journal of Psychosocial Rehabilitation, 2020)
In this article,the increase of food value of meat minced half-finished products with addition of vegetable powder is considered. The reasonability of using the powder in the production of minced meat semi- finished products is justified. Adding pumpkin and pumpkin-carrot powder to the recipe of the cutlets increases the content of carbohydrates by 14.4% and 27.8% respectively. The protein content is not significantly changed, while there is a decrease in fat content in cutlets with the addition of vegetable powder. In addition, mass losses during heat treatment are reduced and organoleptic characteristics (juiciness, consistency, smell, taste) are improved.